PEMODELAN KASUS DIARE DI PROVINSI BALI DENGAN METODE ANALISIS REGRESI SPASIAL - SULASIH, I.G.A. DIAH; SUSILAWATI, MADE; SUCIPTAWATI, NI LUH PUTU (E-Jurnal Matematika; Vol 10 No 2 (2021)DO - 10.24843/MTK.2021.v10.i02.p327, 2021)
Diarrhea is a disease that occurs due to changes in the frequency of bowel movements and can cause death. In 2018, 115.889 cases of diarrhea were found in Bali Province. Information on the relationship between locations indicates the spatial effect in the model. Model estimation was done by using spatial regression analysis. This study aims to determine what factors influence diarrhea cases in Bali Province. The results show that the number of diarrhea cases in a district is influenced by the surrounding districts. This is reinforced in the Moran’s I test which shows spatial dependence. In the analysis of the Spatial Error Model (SEM), it was obtained that the value of  was 57,69% and the variables that significantly affected diarrhea cases in Bali Province were population density and sanitation facilities